INNOVATIVE TENDENCIES AND TRANSFORMATIONS OF FU BAOSHI’S PAINTING DURING THE PERIOD OF HIS RESIDENCE IN SYCHUAN PROVINCE (40S OF THE 20TH CENTURY) - ТЕН, Сіяоджон (Art and Design, 2023)
The aim of this study is to investigate the process of transformation of Fu Baoshi’s artistic style during his residency in Chongqing, Sichuan Province, under the influence of the modernist tendencies of Chinese painting in the early 20th century. Comparative analysis of Fu Baoshi’s works in the comparative context of the development of Chinese painting in the 20th century. Art-historical analysis of artistic and plastic characteristics of stylistically related works with regards to thematic unity, composition, applied painting techniques and means. The artistic and plastic characteristics of Fu Baoshi’s works after his relocation to Sichuan Province demonstrate a unity reflected in thematic content, composition, applied painting techniques and means. Stylistically, his painting practice during that period was characterized by expressive innovative approaches influenced by the local landscape features and the aesthetic program of contemporary society. The following aspects of Fu Baoshi’s artistic activity were explored: thematic range of works, their compositional characteristics, innovation of artistic language, and the possibilities of using painting material for the transformation of individual practice. Globalized synthetic considerations on the painting methods of contemporary artists were projected onto Fu Baoshi’s landscape experience acquired in Sichuan Province. Among the numerous works produced during his Sichuan period, special attention is given to the series «Rainy Landscape», in which the master’s innovative and transformative tendencies are particularly vivid. Scientific novelty. It has been established that the innovative tendencies of Fu Baoshi’s artistic practice can be characterized as an important stage in the formation of a new individual technique of landscape painting, which was later named as «Baoshi Cun.» The results of this research will contribute to a new assessment of Fu Baoshi’s contribution to the treasury of world art.